Comparative Study on Magnetic Activated Carbon Derived from Delignified and Non-delignified Palm Kernel Shell: Synthesis, Characterization, and Methylene Blue Adsorption Analysis - Waluyo, Joko; Nabila, Zahrani Putri; Putra, Ariadi Indra; Purba, Ibnu Tryansar; Izzulhaq, Muhammad Ghozy; Kurnia, Irwan; Septian, Ardie; Ernawati, Lusi (Journal of Engineering and Technological Sciences, 2025)
Indonesia is the global leader in palm oil production, but it deals with significant challenges in managing palm oil mill waste, particularly palm kernel shells (PKS). This study investigated palm kernel shell (PKS) as a precursor for synthesizing magnetic activated carbon (MAC) to enhance its performance as an adsorbent for liquid waste treatment.  The precursor was delignified using alkali liquor and magnetized by incorporating Fe²⁺ and Fe³⁺ ions, followed by chemical activation (ZnCl₂) through an intermediate pyrolysis process. The performances of delignified and non-delignified MAC (DMAC and NDMAC) were evaluated through methylene blue adsorption tests (25–45 mg/L), focusing on adsorption capacity, dye removal efficiency, as well as isotherm and kinetic analysis. DMAC demonstrated a larger surface area, leading to enhanced adsorption performance. Morphological analysis revealed that delignification had a positive influence on the pore structure and size, resulting in a more uniform distribution. DMAC exhibited an adsorption capacity 16.3% higher (35.3 mg/g) in the equilibrium phase and 16.6% higher at maximum adsorption capacity (50.25 mg/g) according to the Langmuir isotherm. Furthermore, the inclusion of iron ions (Fe2+/Fe3+) promoted pore expansion and formation in the precursor material. The study found the Langmuir isotherm model (R² = 0.999) to be the best fit for methylene blue adsorption, while the pseudo-second-order kinetic model (R² = 0.9958) demonstrated an excellent fit for adsorption kinetics. The findings confirm that DMAC and NDMAC derived from PKS are effective for methylene blue dye adsorption, technically.